First small-molecule PROTACs for G protein-coupled receptors: inducing α1A-adrenergic receptor degradation - Zhenzhen Li; Yuxing Lin; Hui Song; Xiaojun Qin; Zhongxia Yu; Zheng Zhang; Gaopan Dong; Xiang Li; Xiaodong Shi; Lupei Du; Wei Zhao; Minyong Li (Elsevier, 2020)
Proteolysis targeting chimeras (PROTACs) are dual-functional hybrid molecules that can selectively recruit an E3 ubiquitin ligase to a target protein to direct the protein into the ubiquitin-proteasome system (UPS), thereby selectively reducing the target protein level by the ubiquitin-proteasome pathway. Nowadays, small-molecule PROTACs are gaining popularity as tools to degrade pathogenic protein. Herein, we present the first small-molecule PROTACs that can induce the α1A-adrenergic receptor (α1A-AR) degradation, which is also the first small-molecule PROTACs for G protein-coupled receptors (GPCRs) to our knowledge. These degradation inducers were developed through conjugation of known α1-adrenergic receptors (α1-ARs) inhibitor prazosin and cereblon (CRBN) ligand pomalidomide through the different linkers. The representative compound 9c is proved to inhibit the proliferation of PC-3 cells and result in tumor growth regression, which highlighted the potential of our study as a new therapeutic strategy for prostate cancer.